Herpes zoster como efeito colateral do tratamento da leishmaniose tegumentar americana com antimonial pentavalente - Barros, Andrea Barbieri de (2009)
Cutaneous leishmaniasis is an endemic disease that affects a significant number of people each year around the world. The first-line treatment is based on the use of antimony drugs. This group of drugs has several adverse effects. Recently, varicella-zoster vírus reactivation has been reported in isolated casesand related to leishmaniais treatiment wich pentavalent antimonials. This study describes 16 patients who had herpes zoster during or shortly after the use of antimony. Among them, 15 (93.8%) were male, with median (range) of 53.3 (22-81) years. Most (75%) had herpes zoster related to meglumine antimoniate and 25% to sodium stibogluconate. The median (range) of onset of herpes zoster lesions was 22.1 (8-36) days. No differences were observed between the two compounds on the dose administered or the time of onset of herpetic lesions. Itcan be concluded that the treatment of tegumentary leishmaniasis withpentavalent antimony, including meglumine antimoniate, is associated with the occurrence of reactivation of varicella-zoster virus. This complication may occur during or after several days of the medication interruption.